SCORECARD PENGUKURAN KINERJA FUNGSIONALSISTEM INFORMASI PEMERINTAH DAERAH - Usman, Usman; Pakarti, Piji (Proceeding SENDI_U, 2016)
Information systems (IS) function is defined as all individuals, group, or department in anorganisation dailyresponsible for information systems related activities in the organisation. This paper presents the development of ascorecard to measure the IS function’s performance in the local government organization.This research is intendedto produce a comprehensive scorecard to measure the functional performance of information systems in publicorganizations.It is based on a theoretical input–outputmodel of the IS function’s role in supporting organizationaleffectiveness and IS Success. Founded on literature study in the areas of e-Government index, IS success, ISorganisation’s effectiveness, IS resources and capability, and IS function performance, 106 performance items wereidentified. 207 data set from 15local goverment institutions (SKPD) were used to validate the measurementinstrument. The resulted performance scorecard covers five main dimensions, namely:1) Governance and Policy, 2)Service Quality, 3) System Quality, 4) Information Quality and 5)Individual amd Organizational Impact. This studyhighlights the importance of governance and policy aspects to increase the performance of the IS function,especially related to the capability of IS function to perform a good quality planning, effective system adaptationand good operational support.Keywords: Scorecard, Functional Performance, Information System, Local Government Institution